Impacts of Camellia kucha and its main chemical components on the lipid accumulation in 3T3‐L1 adipocytes. (13th October 2016) - Li, Kai Kai; Wong, Hing Lok; Hu, Tianyong; Zhang, Cheng; Han, Xiao Qiang; Ye, Chuang Xing; Leung, Ping Chung; Cheng, Bao Hui; Ko, Chun Hay
Summary: Camellia kucha, a wild tea plant with potent antioxidant potential, has been consumed as local beverage for a long history. It is featured for the presence of theacrine and low content of caffeine. Interestingly, compared with caffeine showed strong stimulant effect, theacrine showed sedation, hypnoses and promoting memory function. In this study, the anti‐adipogenic ability of Kucha tea (KT) and its main components were evaluated in mouse 3T3‐L1 cells. The results indicated that KT acted significantly to decrease lipid droplet accumulation. Moreover, KT decreased the expression of major transcription factors of adipogenesis pathway, such as PPAR γ and C/EBP α. KT also decreased the mRNA and protein levels of fatty acid synthase, fatty acid translocase, steroylcoenzyme A desaturase‐1, lipoprotein lipase and acetyl‐CoA carboxylase‐1. Furthermore, KT suppressed the activation of ERK, p38 and JNK. Abstract : KT, as a new natural functional food, possesses the potential to inhibit cell viability and adipocyte differentiation in 3T3‐L1 cells in a dose‐dependent manner. The mechanism studies indicated that the anti‐adipogenic activity of KT was exerted by the PPAR c and CEBP a via inhibition of ERK, p38 and JNK activation.